Effects of Problem-Based and Guided Inquiry Learning on Vocational Students’ Critical Thinking Skills - Rosa Meilani; Adi Nurcahyo; Mohamad Waluyo (Jurnal Inovasi Matematika, 2026)
In the modern era, critical thinking is a key skill for success in both academic and professional contexts. This study investigates the critical thinking abilities of Vocational High School (SMK) students, which remain relatively low, as reflected in their difficulties solving contextual problems and presenting logical mathematical reasoning. The research aims to examine the effects of the Problem-Based Learning (PBL) and Guided Inquiry (GI) models on students’ critical thinking skills in learning circle geometry. Using a quasi-experimental design, the study involved 11th-grade students at SMK Negeri 1 Boyolali. Class XI MPLB 2 served as the experimental group using the PBL model, while Class XI PM 2 acted as the control group using the GI model. Data were collected through pre-tests, post-tests, and documentation, and analyzed using the independent samples t-test, normality test, and N-Gain test. The results showed a significant difference between the two groups: the PBL class achieved a higher average post-test score (60.91) than the GI class (43.28). The t-test results (t = 4.461, p < 0.05) confirmed that PBL was more effective than GI in improving students’ critical thinking skills, although both models produced outcomes in the low N-Gain category.